Restrictions on the Internet Freedom in Turkey - Katalin, Siska (UNIB Press, 2023)
Turkey's Internet has 42.3 million active users and holds a 'Not Free' ranking in Freedom House's index. The Turkish Government has constantly blocked websites like Facebook, Twitter, YouTube, and Wikipedia. According to Twitter's transparency report, Turkey leads in social media censorship. Reporters Without Borders ranked Turkey 149th out of over 180 countries, between Mexico and DR Congo, with a score of 44.16. In my study, I summarize the legislative amendments of recent years that apply to internet regulation, with particular regard to those rules that allow the restriction of internet freedom. I pay special attention to the institutional changes that followed these amendments.